Meaningful work in a post-Covid age : the impact of new technologies - Buszka, Sharlene; Ewest, Timothy (Emerald Publishing Limited, 2025)
The Covid-19 pandemic triggered an unprecedented shift to remote work, made possible by a vast array of technologies. While the frequency of remote work has decreased post-pandemic, many workers and organizations are now embracing remote and hybrid work options. Technologies that proved beneficial during the pandemic continue to be used, and the explosion of AI across industries has left many wondering about the future of work and society. Meaningful Work in a Post-Covid Age: The Impact of New Technologies presents examples of how technology can enhance efficiency and effectiveness in education, industry, and healthcare when used to support organizational stakeholders. However, it also cautions that we must consider the long-term impact of technology on human well-being. The widespread use of new technologies has resulted in lasting shifts in organizational and worker mindsets about what is considered normal, appropriate, and desirable in how and where work is performed. These changes have also impacted how meaningful work is experienced. The book addresses the underlying concern about whether the pervasive use of technology will result in net benefits or losses to society. Technology that focuses primarily on efficiency at the expense of relational and creative needs can detract from the meaningfulness of life and work, leading to worker unrest and alienation, and potentially impacting the physical and mental health of the global population. Meaningful Work in a Post-Covid Age presents models and tools to help leaders, decision-makers, and workers navigate their organizations and careers to find meaningful work amidst the accelerating growth of new technologies.
Includes index.
Keywords: Labor -- Technological innovations.; Business & Economics -- Labor -- General.; Business innovation.; Labour, income economics.; Industrial relations, occupational health and safety.; elektronické knihy; electronic books